2007
DOI: 10.1016/j.ijgo.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Low first‐trimester hemoglobin and low birth weight, preterm birth and small for gestational age newborns

Abstract: Low first-trimester Hb concentration increases the risk of LBW, preterm birth and SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
1
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 26 publications
2
117
1
18
Order By: Relevance
“…Levy et al, for example, observed that maternal anemia was an independent risk factor for preterm delivery and low birth weight (7). In China, low hemoglobin concentration was associated with increased risk for preterm birth, small-for-gestational-age foetuses and low birth weight (8). Women with anemia had infants who were at higher risk of having a low birth weight and foetal growth restrictions than infants born to non-anemic women (9).…”
Section: Introductionmentioning
confidence: 99%
“…Levy et al, for example, observed that maternal anemia was an independent risk factor for preterm delivery and low birth weight (7). In China, low hemoglobin concentration was associated with increased risk for preterm birth, small-for-gestational-age foetuses and low birth weight (8). Women with anemia had infants who were at higher risk of having a low birth weight and foetal growth restrictions than infants born to non-anemic women (9).…”
Section: Introductionmentioning
confidence: 99%
“…35.41% (17/48) patient who survived develop puerperal sepsis, post-partum hemorrhage, septicemia which necessitates ICU care for these patients. Fetal outcome was also compared with study by Ren et al (2007) which showed increased risk of low birth weight, pre-term and intrauterine growth restriction in patients with low first trimester hemoglobin concentration. 5 Kidanto et al (2009) reported increased incidence of preterm and intrauterine growth restriction with increased degree of severity of anemia, 6 these results were comparable with our study in which most of the preterm ,intra-uterine growth restriction and dead born neonates were seen in patient with severe anemia.…”
Section: Resultsmentioning
confidence: 99%
“…Fetal outcome was also compared with study by Ren et al (2007) which showed increased risk of low birth weight, pre-term and intrauterine growth restriction in patients with low first trimester hemoglobin concentration. 5 Kidanto et al (2009) reported increased incidence of preterm and intrauterine growth restriction with increased degree of severity of anemia, 6 these results were comparable with our study in which most of the preterm ,intra-uterine growth restriction and dead born neonates were seen in patient with severe anemia. Fall in maternal hemoglobin <8 gm/dl were associated with significant rise in perinatal mortality rate, fall in birth weight due to increase in prematurity rate and intrauterine growth restriction.…”
Section: Resultsmentioning
confidence: 99%
“…(19) tarafından yapılan popülasyon temelli başka bir çalışmada ise, ilk trimester Hb düze-yi ile düşük doğum ağırlığı (LBW), preterm ve SGA ilişkisi sorgulanmıştır. Bu çalışmada anemi prevalansı %22,1 olarak bulunmuştur.…”
Section: Discussionunclassified